TEORI PEMIKIRAN EKONOMI KLASIK “THE INVISIBLE HAND” DAN RELEVANSINYA PADA APBN DI INDONESIA (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2023)
Adam Smith was a classical economist who was born in the middle of the 18th century. The market mechanism regulates all economic activities, such as production, distribution, and consumption. In the market mechanism, there is a “tug of war” in the process of economic activity thereby market will reach its equilibrium independently. The process, according to Smith, is controlled by an “invisible hand” that regulates market equilibrium. However, achieving a market balance by the “invisible hand” is a thing that is very hard to prove. Market failure will occur if the market is always left independent. Market failure can be marked by the appearance of imperfect competition market and externality. From here, it can be concluded that the role of The Government is considered very crucial to preserve the continuity of economic activity and to prevent market failure. In this case, APBN, or State Budget is one of the Indonesian Government’s efforts to regulate economic activity. Thus, economic equilibrium can be gained and social welfare can be reached. Keywords: Adam Smith, The Invisible Hand, APBN